Evidence-based efficacy of methotrexate in adult Crohn's disease in different intestinal and extraintestinal indications. (March 2022) - Cassinotti, Andrea; Batticciotto, Alberto; Parravicini, Marco; Lombardo, Maurizio; Radice, Paolo; Cortelezzi, Claudio Camillo; Segato, Simone; Zanzi, Federico; Cappelli, Antonella; Segato, Sergio
Introduction: Methotrexate (MTX) is included in the therapeutic armamentarium of Crohn's disease (CD), although its positioning is currently uncertain in an era in which many effective biological drugs are available. No systematic reviews or meta-analysis have stratified the clinical outcomes of MTX according to the specific clinical scenarios of its use. Methods: Medline, PubMed and Scopus were used to extract eligible studies, from database inception to May 2021. A total of 163 studies were included. A systematic review was performed by stratifying the outcomes of MTX according to formulation, clinical indication and criteria of efficacy. Results: The use of MTX is supported by randomized clinical trials only in steroid-dependent CD, with similar outcomes to thiopurines. The use of MTX in patients with steroid-refractoriness, failure of thiopurines or in combination with biologics is not supported by high levels of evidence. Combination therapy with biologics can optimize the immunogenic profile of the biological drug, but the impact on long-term clinical outcomes is described only in small series with anti-TNFα. Other off-label uses, such as fistulizing disease, mucosal healing, postoperative prevention and extraintestinal manifestations, are described in small uncontrolled series. The best performance in most indications was shown by parenteral MTX, favouring higher doses (25 mg/week) in the induction phase. Discussion: Evidence from high-quality studies in favour of MTX is scarce and limited to the steroid-dependent disease, in which other drugs are the leading players today. Many limitations on study design have been found, such as the prevalence of retrospective underpowered studies and the lack of stratification of outcomes according to specific types of patients and formulations of MTX. Conclusion: MTX is a valid option as steroid-sparing agent in steroid-dependent CD. Numerous other clinical scenarios require well-designed clinical studies in terms of patient profile, drug formulation and dosage, and criteria of efficacy.